Preferensi Preferensi Pemangsaan Drupella sp. pada Jenis Karang yang Berbeda di Perairan Pemuteran, Bali - Ni Wayan Gita Kanela; IGN Putra Dirgayusa; Widiastuti Karim (Journal of Marine Research and Technology, 2018)
Coral reefs are experiencing dynamic changes over time that are strongly influenced by environmental conditions and human activities. One of the natural damage to coral reefs is corallivorous gastropods such as Drupella sp. The marine tourism of Pemuteran waters on northern part of Bali is rapidly developing. However the Bio-Rock Center reported that there were 2.374 individuals of Drupella sp. found during 2008-2009 in this water. Therefore, this study aimed to determine the densities of Drupella sp. and prey preferences of Drupella sp. on coral species in Pemuteran waters. There were 4 observation sites that parallel to the shoreline at similar depths (5-6 m). The densities of Drupella sp. and prey preference were measured 2 x 20 m belt transect by using SCUBA. Live coral covers were counted in LIT (Line Intercept Transect) method. The significant difference of Drupella sp. densities among sites was analysed by using one way ANOVA, while the prey preference among corals species was identified by using Bonferroni test. The result showed that the highest abundance of Drupella sp. found at station 1 and the lowest at station 2. It is suggested that related to percentage of live coral cover as the highest was at station 1 and the lowest was at station 2.Studies revealed that Drupella sp. prey particulary on living coral. Furthermore, our observations indicated that Drupella sp. more attracted to coral Porites and Pocillopora. This prey preferences are thought to be due to the highest abundance of these corals at all study sites.